Acquisitions Driven by Stock Overvaluation - LIN, Leming (Institutional Knowledge at Singapore Management University, 2009)
Overvaluation might drive a firm to use its stock to acquire another firm whose stock is not as overpriced. Though hypothetically desirable, these acquisitions create little, if any, value for acquirer shareholders. Two factors impede value creation for acquirer stockholders from these transactions (despite large differences in relative overvaluation at announcement): acquirers paying large premiums to targets, and investors' correction of acquirer overvaluation during the bid period. Furthermore, acquirer CEOs obtain a large amount of new stock and option grants after acquisitions and realize a net gain in wealth, further suggesting that equity overvaluation increases agency costs and the resulting actions benefit managers more than shareholders (Jensen (2005)).